REFLEKSI MODEL SIX THINKING HATS SEBAGAI UPAYA PERBAIKAN PEMBELAJARAN ILMU PENGETAHUAN ALAM (IPA) - Riswakhyuningsih, Tri (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2025)
The Six Thinking Hats model looks at one topic from multiple perspectives. The purpose of the research is to reflect on science learning with the Six Thinking Hats model. The research was conducted using descriptive method. Conducting a critical analysis of the learning process in the 2021/2022 to 2023/2024 school years. Reflection on learning in the 2021/2022 academic year: 1) Fact: face-to-face learning is limited, 2) Feelings: thinking more to prepare a limited face-to-face learning strategy, 3) Positive things: being able to meet face-to-face with students, 4) Obstacles: making learning scenarios to achieve student competencies, 5) Ideas that arise: Implementing a flipped classroom approach, applying the principle of alam takambang jadi guru, 6) Conclusion: learning time and place are more flexible, student competencies are achieved. Reflection on learning for the 2022/2023 academic year: 1) Fact: first year of IKM, 2) Feelings: adapting to curriculum changes, 3) Positive things: students can explore and express their learning interests, Pancasila learner profile grows, 4) Obstacles: identifying students' learning styles, 5) Ideas: implementing differentiated learning with multiple strategies, 6) Conclusion: students learn according to their learning styles. Reflection on learning in the 2023/2024 academic year:1) Fact: second year of IKM, 2) Feelings: freedom to design learning, 3) Positive things: adaptive and flexible learning process, 4) Obstacles: encouraging students' active participation, 5) Ideas: creating activity-based learning, 6) Conclusion: learning activities have increased. Keywords: Reflection, Learning Science, Six Thinking Hats